The Effect of Taxation Socialization and e-Billing on Land and Building Taxpayer Compliance (Case Study in Pematang Johar Village, Medan) - Sanjaya, Vamelia; Susan Grace V. Nainggolan; Dr. Thuy Ha Thi (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine whether Taxation Socialisation and E-Billing significantly affect Land and Building Taxpayer Compliance. This study uses quantitative data methods, and the primary data source is primary data. The population in this study was people from Pematang Johar Village. The sample of this study consisted of 130 respondents who used accidental sampling data collection techniques. Data analysis and testing consist of a validity test, reliability test, descriptive statistical test, classical assumption test, multiple regression analysis, partial hypothesis testing (T-test) and simultaneously (F test), and determination coefficient test. The results showed that Taxation Socialisation has a partially significant effect on Land and Building Taxpayer Compliance with a T value of 3.631> T table 1.98447. E-billing significantly affects land and building taxpayer compliance with a T count of 9.694> T table 1.98447. Taxation Socialisation and E-Billing simultaneously significantly affect Land and Building Taxpayer Compliance with an F value of 48,498> F table value of 3.09 and a regression coefficient value of 50.5%.